Nano-modification to improve the ductility of cementitious composites. (October 2015) - Yeşilmen, Seda; Al-Najjar, Yazin; Balav, Mohammad Hatam; Şahmaran, Mustafa; Yıldırım, Gürkan; Lachemi, Mohamed
Abstract: Effect of nano-sized mineral additions on ductility of engineered cementitious composites (ECC) containing high volumes of fly ash was investigated at different hydration degrees. Various properties of ECC mixtures with different mineral additions were compared in terms of microstructural properties of matrix, fiber-matrix interface, and fiber surface to assess improvements in ductility. Microstructural characterization was made by measuring pore size distributions through mercury intrusion porosimetry (MIP). Hydration characteristics were assessed using thermogravimetric analysis/differential thermal analysis (TGA/DTA), and fiber-matrix interface and fiber surface characteristics were assessed using scanning electron microscopy (SEM) through a period of 90 days. Moreover, compressive and flexural strength developments were monitored for the same period. Test results confirmed that mineral additions could significantly improve both flexural strength and ductility of ECC, especially at early ages. Cheaper Nano-CaCO3 was more effective compared to nano-silica. However, the crystal structure of CaCO3 played a very important role in the range of expected improvements.